Kearifan Lokal dalam Novel ‘Sayat-Sayat Sunyi’ Karya S.Gegge Mappangewa : Local Wisdom in the Novel 'Sayat-Sayat Sunyi' by S. Gegge Mappangewa - Nurrahmawanda, Nurrahmawanda; Hamsa, Akmal; Usman, Usman (Journal Studies in Indonesian Language and Literature, 2025)
This study aims to identify the forms of local wisdom and the values of local wisdom in the novel "Sayat-Sayat Sunyi" by S. Gegge Mappangewa. This research is a qualitative study using a literary anthropology approach. Data acquisition was carried out through repeated readings and thematic analysis of the characters, narrative, and dialogue in the novel "Sayat-Sayat Sunyi."The results of the study on local wisdom in the novel "Sayat-Sayat Sunyi" by S. Gegge Mappangewa are as follows: (1) Forms of local wisdom include the human equipment system encompassing traditional dwellings, productive tools or tools to meet needs, traditional clothing, and traditional lighting. The livelihood system includes farmers, traders, and "sanro wanua" (village healers). The community and organizational system encompasses kinship systems and certain social groups. The arts include Bugis poetry and "lambaru" (traditional dance or music). The knowledge system includes knowledge related to the flora and fauna. The religious system includes beliefs in God and religious rituals. Language includes the use of honorifics like "daeng" and "ambo." (2) The values of local wisdom include cultural values encompassing customs or traditions. Social values include mutual cooperation, helping each other, and care. Religious values include beliefs or traditions in conducting activities during certain months in the Hijri calendar and customs or traditions related to the Hajj pilgrimage among the Bugis community.